A Modest Proposal to Save the Double Jeopardy Clause - George C. Thomas III (Washington University Law Quarterly, 1991)
Though it did not attract much attention, one of Justice Brennan's last majority opinions for the Supreme Court effected a major change in the long-standing interpretation of the double jeopardy clause. Brennan's opinion in Grady v. Corbin affirmed a position I had taken in previous articles, namely that the double jeopardy clause provides some form of protection against reprosecution of the same conduct. I still believe the principle correct. But I also believe the lack of articulated limitations on the principle renders the 5-4 decision in Corbin unstable because, if unchecked, it will lead to results that are contrary to our shared intuitions about what double jeopardy should forbid. Thus, while I would not phrase it quite the same way, I agree in essence with Justice Scalia's pre-diction of the societal response to Corbin: "rejection of today's [majority] opinion is adequately supported by the modest desire to protect our criminal legal system from ridicule." Moreover, I agree with Scalia's prediction of Corbin’s future if it remains in its current form: "A limitation that is so unsupported in reason and so absurd in application is unlikely to survive." But if a future Court reverses Corbin on the grounds that Scalia suggests, the result will be to narrow severely the protection of the clause. Thus, I wish to discuss how Corbin is simultaneously right and wrong. Then I will propose a solution to this dilemma, one that avoids Scalia's narrow dissenting position and derives from the literal language of the double jeopardy clause.
Keywords: Double jeopardy